The Impact of Exchange Rate Changes on the Real Sphere of the Polish Economy in 2010–2019 - Markowski, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The aim of the study is to assess the impact of changes in the EUR/PLN exchange rate on the real sphere of the Polish economy in 2010–2019. This period was characterized by a relatively stable macroeconomic situation between the two world economic crises. The Polish economy can also be assessed at that time as relatively closely related in terms of trade, money and economic conditions with the euro area, which is confirmed by the literature review. The first part of the article describes the phenomena that determine the functioning of the exchange rate as a mechanism for stabilizing the economic situation in Poland and presents selected research results in this area. The next part of the work is devoted to the description of the methodology of the author’s own research. Then the obtained results and conclusions were presented. The study used the VAR econometric model, which did not show a statistically significant relationship between changes in the EUR/PLN exchange rate and changes in real GDP.